Effect of Physical Activity, Social Support, and Skills Training on Late-Life Emotional Health: A Systematic Literature Review and Implications for Public Health Research - Snowden, Mark B.; Steinman, Lesley E.; Carlson, Whitney L.; Mochan, Kara N.; Abraido-Lanza, Ana F.; Bryant, Lucinda L.; Duffy, Michael; Knight, Bob G.; Jeste, Dilip V.; Leith, Katherine H.; Lenze, Eric J.; Logsdon, Rebecca G.; et al. (Frontiers in Public Health, 2015)
Given that emotional health is a critical component of healthy aging, we undertook a systematic literature review to assess whether current interventions can positively affect older adults' emotional health. A national panel of health services and mental health researchers guided the review. Eligibility criteria included community-dwelling older adult (aged ≥ 50 years) samples, reproducible interventions, and emotional health outcomes, which included multiple domains and both positive (well-being) and illness-related (anxiety) dimensions. This review focused on three types of interventions - physical activity, social support, and skills training - given their public health significance and large number of studies identified. Panel members evaluated the strength of evidence (quality and effectiveness). In all, 292 articles met inclusion criteria. These included 83 exercise/physical activity, 25 social support, and 40 skills training interventions. For evidence rating, these 148 interventions were categorized into 64 pairings by intervention type and emotional health outcome, e.g., strength training targeting loneliness or social support to address mood. 83% of these pairings were rated at least fair quality. Expert panelists found sufficient evidence of effectiveness only for skills training interventions with health outcomes of decreasing anxiety and improving quality of life and self-efficacy. Due to limitations in reviewed studies, many intervention-outcome pairings yielded insufficient evidence. Skills training interventions improved several aspects of emotional health in community-dwelling older adults, while the effects for other outcomes and interventions lacked clear evidence. We discuss the implications and challenges in moving forward in this important area.